2018
DOI: 10.1038/s41419-018-0991-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcription coactivator Cited1 acts as an inducer of trophoblast-like state from mouse embryonic stem cells through the activation of BMP signaling

Abstract: Trophoblast lineages, precursors of the placenta, are essential for post-implantation embryo survival. However, the regulatory network of trophoblast development remains incompletely understood. Here, we report that Cited1, a transcription coactivator, is a robust inducer for trophoblast-like state from mouse embryonic stem cells (ESCs). Depletion of Cited1 in ESCs compromises the trophoblast lineage specification induced by BMP signaling. In contrast, overexpression of Cited1 in ESCs induces a trophoblast-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…30 Moreover, various TF cofactors including Cited1, Nfkbia, and Lmo4 were also identified in FGCs ( Figure 3A), and these cofactors could interact with numerous TFs that are highly expressed in FGCs to regulate early oogenesis. [31][32][33] Dynamic cell cycle regulation is crucial for FGC development. Our data indicated that the cell cycle genes in meiocytes underwent complex regulations and they were very different compared to those in somatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…30 Moreover, various TF cofactors including Cited1, Nfkbia, and Lmo4 were also identified in FGCs ( Figure 3A), and these cofactors could interact with numerous TFs that are highly expressed in FGCs to regulate early oogenesis. [31][32][33] Dynamic cell cycle regulation is crucial for FGC development. Our data indicated that the cell cycle genes in meiocytes underwent complex regulations and they were very different compared to those in somatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Cited2, both Cited1 and Cited4 are poorly expressed in undifferentiated ESC and might not play a major role in the maintenance of the pluripotency [43,46]. Moreover, Cited1 overexpression in mouse ESC triggers their transition to a trophoblast-like state by activation of a trophoblast transcriptional program [43]. In undifferentiated mouse ESC, Cited2 directly controls the expression of Nanog, Tbx3 and Klf4 transcripts and the promoter activity of these genes (Figures 1 and 2, and Table 1), and in turn, Nanog activates Cited2 promoter activity [38].…”
Section: Maintenance Of Pluripotent Statementioning
confidence: 99%
“…Conversely, Cited2 acute depletion not only impairs proliferation, but also triggers cell death by apoptosis and spontaneous differentiation of ESC [38]. Unlike Cited2, both Cited1 and Cited4 are poorly expressed in undifferentiated ESC and might not play a major role in the maintenance of the pluripotency [43,46]. Moreover, Cited1 overexpression in mouse ESC triggers their transition to a trophoblast-like state by activation of a trophoblast transcriptional program [43].…”
Section: Maintenance Of Pluripotent Statementioning
confidence: 99%
See 2 more Smart Citations